Purinergic signaling in the gastrointestinal tract - Burnstock, Geoffrey (Baishideng Publishing Group Co., Limited, 2011)
Geoffrey Burnstock completed a BSc at King’s College London and a PhD at University College London. He held postdoctoral fellowships with Wilhelm Feldberg (National Institute for Medical Research), Edith Bülbring (University of Oxford) and C. Ladd Prosser (University of Illinois). He was appointed to a Senior Lectureship in Melbourne University in 1959 and became Professor and Chairman of Zoology in 1964. In 1975 he became Head of Department of Anatomy and Developmental Biology at UCL and Convenor of the Center of Neuroscience. He has been Director of the Autonomic Neuroscience Institute at the Royal Free Hospital School of Medicine since 1997. He was elected to the Australian Academy of Sciences in 1971, the Royal Society in 1986, the Academy of Medical Sciences in 1998 and an Honorary Fellow of the Royal College of Surgeons and the Royal College of Physicians in 1999 and 2000. He was awarded the Royal Society Gold Medal in 2000. He is editor-in-chief of the journals Autonomic Neuroscience and Purinergic Signalling and on the editorial boards of many other journals. Geoffrey Burnstock’s major research interest has been autonomic neurotransmission and he is best known for his seminal discovery of purinergic transmission and receptors, their signaling pathways and functional relevance. He has supervised over 100 PhD and MD students and published over 1400 original papers, re-views and books. He was first in the Institute of Scientific Information list of most cited scientists in Pharmacology and Toxicology from 1994-2004 [59.083 citations (March 2011) and an h-index of 109].